Functional Specialization of Duplicated AGAMOUS Homologs in Regulating Floral Organ Development of Medicago truncatula - Zhu, Butuo; Li, Hui; Wen, Jiangqi; Mysore, Kirankumar S.; Wang, Xianbing; Pei, Yanxi; Niu, Lifang; Lin, Hao (Frontiers in Plant Science, 2018)
The C function gene AGAMOUS (AG) encodes for a MADS-box transcription factor required for floral organ identity and floral meristem (FM) determinacy in angiosperms. Unlike Arabidopsis, most legume plants possess two AG homologs arose by an ancient genome duplication event. Recently, two euAGAMOUS genes, MtAGa and MtAGb, were characterized and shown to fulfill the C function activity in the model legume Medicago truncatula. Here, we reported the isolation and characterization of a new mtaga allele by screening the Medicago Tnt1 insertion mutant collection. We found that MtAGa was not only required for controlling the stamen and carpel identity but also affected pod and seed development. Genetic analysis indicated that MtAGa and MtAGb redundantly control Medicago floral organ identity, but have minimal distinct functions in regulating stamen and carpel development in a dose-dependent manner. Interestingly, the stamens and carpels are mostly converted to numerous vexillum-like petals in the double mutant of mtaga mtagb, which is distinguished from Arabidopsis ag. Further qRT-PCR analysis in different mtag mutants revealed that MtAGa and MtAGb can repress the expression of putative A and B function genes as well as MtWUS, but promote putative D function genes expression in M. truncatula. In addition, we found that the abnormal dorsal petal phenotype observed in the mtaga mtagb double mutant is associated with the upregulation of CYCLOIDEA (CYC)-like TCP genes. Taken together, our data suggest that the redundant MtAGa and MtAGb genes of M. truncatula employ a conserved mechanism of action similar to Arabidopsis in determining floral organ identity and FM determinacy but may have evolved distinct function in regulating floral symmetry by coordinating with specific floral dorsoventral identity factors.